From the general managerial skills to the school manager’s skills - Stan, Cristina (Annals of Spiru Haret University. Economic Series, 2016)
Training and skill development represents a process in progress during the whole career and involves specialized training both within the organization and throughout the professional and social environment. Notion of skill/ com-petence has been the object of investigation for many sciences. Clarification of notion of competence/skill is necessary for those who want to deal with compe-tences, no matter is about their competences or of the others. In cognitive psychology and in educational sciences, in ergonomics and in economy or in human resources management, the concept of skill or competence is situated in the middle of the individual and collective performance and all of us want to develop. In education, the art of management is very important because it better highlights the principle’s/ school manager’s personality and his/ her personal example has an essential role in realizing the established objectives for school. The art of running a school is in fact the art of working with people that means a new, modern and distinct dimension of the one who runs the education institution.